2019
DOI: 10.1177/2516598419829593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various factors influencing the generation of hemispherical micro features using non-conformal RMEDM

Abstract: Non-conformal reverse micro electrical discharge machining (NC-RMEDM) is a variant of conventional RMEDM developed by the present authors wherein modification in the tool is carried out to generate different shapes of micro features. In this study, the effect of various factors like flat bottom and taper bottom hole, inversing the position of tool and workpiece and changing the hole depth have been experimentally investigated to determine the optimal combination required for generating hemispherical shaped mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Rashed et al [12] used a reverse micro-EDM uses powder metallurgical green compact tool to create a predetermined star-shaped pattern on the aluminum 6061 work surface. Roy et al [13] have studied the influence of several elements, such as flat bottom and taper bottom hole, inverting the location of tool and workpiece, and modifying the hole depth was experimentally explored in this study to identify the ideal combination necessary for manufacturing hemispherical shaped micro features and also discovered that a hemispherical shape micro feature might be created using a tapered bottom blind hole as a tool. Mastud et al [14] concluded that the capacitance controlled the number of pulses per unit of time and energy of sparking and reverse micro-EDM is unstable at very low capacitance (pF) and very high capacitance value (μF).…”
Section: Introductionmentioning
confidence: 99%
“…Rashed et al [12] used a reverse micro-EDM uses powder metallurgical green compact tool to create a predetermined star-shaped pattern on the aluminum 6061 work surface. Roy et al [13] have studied the influence of several elements, such as flat bottom and taper bottom hole, inverting the location of tool and workpiece, and modifying the hole depth was experimentally explored in this study to identify the ideal combination necessary for manufacturing hemispherical shaped micro features and also discovered that a hemispherical shape micro feature might be created using a tapered bottom blind hole as a tool. Mastud et al [14] concluded that the capacitance controlled the number of pulses per unit of time and energy of sparking and reverse micro-EDM is unstable at very low capacitance (pF) and very high capacitance value (μF).…”
Section: Introductionmentioning
confidence: 99%
“…Roy et al [ 18 ] analyzed the physical phenomenon behind occurrences of unusually high discharging points in reverse micro EDM by establishing a numerical model of ions and electrons’ movement in the dielectric during machining. To realize the micro-EDM machining of the three-dimensional structure, Roy et al [ 19 ] used reverse micro EDM to generate different shapes of protruded micro features, such as 3D hemispherical and 3D coni-spherical shapes. To study EDM’s surface characteristics, Hsieh et al [ 2 ] showed that the EDM process could successfully machine the ternary TiNiZr SMAs while ensuring its shape recovery ability.…”
Section: Introductionmentioning
confidence: 99%